As vantagens da implantação de business intelligence na empresa Sapatu´s S/A, indústria do ramo de produção de calçados do interior do estado do Rio Grande do Sul - Michaelsen, Marco Fernando (Universidade do Vale do Rio dos Sinos, 2017)
The current article is intended to present the benefits which the Business Intelligence (BI) tooling provided to a footwear-producing Industry from the interior of Rio Grande do Sul. The difficulties and needs the company used to endure, referring to the promptness and support to the decision-making, have been determining to introduce the idea of using a BI tool but also completely unknown by the enterprise. For your better understanding of the project advantages, some processes inside the company have been mapped before the implantation and compared after it. This it has been possible to demonstrate the Return on Investment (ROI) and the Payback achieved by improving these procedures. The period of comprehensiveness of the work was from April to August of 2017. After the data analysis, it has been established the Business Intelligence tooling usage has a great potential to be explored inside the companies since they are capable to sort out expensive problems and in several times unknown by the enterprises.
Keywords: Tecnologia da Informação; Business Intelligence; ERP; ROI; Payback; Information Technology; Business Intelligence; Enterprise Resource Planning; ERP; Return on Investment; ROI; Payback